PERIODONTITIS: BASIC CONCEPTS - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira (Seven Editora, 2026)
Periodontitis is a multifactorial chronic inflammatory disease characterized by the irreversible destruction of dental support tissues, including the periodontal ligament and alveolar bone. Its etiopathogenesis involves the interaction between a dysbiotic biofilm and an exacerbated host immune-inflammatory response, mediated by pro-inflammatory cytokines, prostaglandins, and metalloproteinases. This chapter describes the mechanisms of tissue destruction, the evolution of the disease, and the participation of the RANK/RANKL/OPG system in bone resorption. It also addresses the 2017 classification of periodontal diseases, highlighting the staging and grading system for periodontitis, as well as necrotizing periodontal diseases. Finally, it emphasizes the importance of clinical and radiographic evaluation for diagnosis, prognosis, and individualized therapeutic planning.